Burn for burn - Han, Jenny .; Vivian, Siobhan (London : Simon & Schuster, 2012)
Critically acclaimed authors Jenny Han - whose New York Times bestseller To All The Boys I've Loved Before inspired the hit NETFLIX movie - and Siobhan Vivian team up in this thrilling trilogy. Perfect for fans of Pretty Little Liars and Big Little Lies
Keywords: Revenge -- Fiction; Friendship -- Fiction; High schools -- Fiction